2018
DOI: 10.1093/gerona/gly090
|View full text |Cite
|
Sign up to set email alerts
|

Age Modulates the Association of Caffeine Intake With Cognition and With Gray Matter in Elderly Diabetics

Abstract: Caffeine intake may have a beneficial role in cognitive functioning of elderly adults with T2D, which may be moderated by age. Greater GM volume may be a mechanism underlying the association of higher caffeine intake with better cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 41 publications
1
31
1
5
Order By: Relevance
“…Kimura et al discovered that L-theanine plays a positive role in anti-stress by reducing stress-induced heart rate and salivary immunoglobulin A (s-lgA) during a stressed mental arithmetic task [3]. The beneficial effect of caffeine on cognitive functioning was reported at least two decades ago [17] and replicated by recent studies [18, 19]. Although individual constituents of tea have been related to the roles of maintaining cognitive abilities and preventing cognitive decline, a study with behavioural and neurophysiological measures showed that there was a degraded effect or no effect when a constituent was administered alone and a significant effect was observed only when constituents were combined [20].…”
Section: Introductionmentioning
confidence: 99%
“…Kimura et al discovered that L-theanine plays a positive role in anti-stress by reducing stress-induced heart rate and salivary immunoglobulin A (s-lgA) during a stressed mental arithmetic task [3]. The beneficial effect of caffeine on cognitive functioning was reported at least two decades ago [17] and replicated by recent studies [18, 19]. Although individual constituents of tea have been related to the roles of maintaining cognitive abilities and preventing cognitive decline, a study with behavioural and neurophysiological measures showed that there was a degraded effect or no effect when a constituent was administered alone and a significant effect was observed only when constituents were combined [20].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh West et al (2019) pada sampel individu lansia dengan diabetes melitus tipe 2 (DM tipe 2), didapatkan bahwa tingkat asupan kafein yang lebih tinggi secara signifikan berkaitan dengan kinerja kognitif yang lebih baik dan volume gray matter yang lebih besar. Asupan kafein memiliki hubungan yang kecil akan tetapi signifikan dengan kognisi keseluruhan (p = 0,018), memori kerja / perhatian (p = 0,002), kategorisasi semantik (p = 0,026), dan fungsi eksekutif (p =.…”
Section: Hasil Dan Pembahasanunclassified
“…Asupan kafein memiliki hubungan yang kecil akan tetapi signifikan dengan kognisi keseluruhan (p = 0,018), memori kerja / perhatian (p = 0,002), kategorisasi semantik (p = 0,026), dan fungsi eksekutif (p =. 047) (West et al, 2019). Hal ini juga sejalan dengan penelitian oleh eskelinen et al (2010), bahwa konsumsi kopi sebanyak 3-5 cangkir per hari memiliki 65-70% penurunan risiko demensia dan 62-64% penurunan risiko penyakit alzheimer dibandingkan dengan konsumsi kopi yang lebih sedikit (p≤ 0,05) (Eskelinen & Kivipelto, 2010).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…They are ubiquitous in human biological fluids [12][13][14], serum/plasma, particularly, cannot be excluded, previous research has reported that trace amounts of CA and/or its several metabolites were detected in serum from normal adults, even in human subjects who had abstained from methylxanthines for 1 week [15][16][17]. Recently, studies have shown that CA is also associated with cognitive function and white matter lesions in the elderly [18][19][20][21][22]. It was reported that serum levels of CA and its metabolites were significantly decreased in patients with early PD [19,23].…”
Section: Introductionmentioning
confidence: 99%